Resolving Structural Ambiguity in English Relative Clauses and Prepositional Phrases - Tarihoran, Irfan Hamonangan; Jazadi, Iwan; Solihin, Solihin (JOLLT Journal of Languages and Language Teaching, 2025)
Structural ambiguity remains a persistent challenge in English comprehension, particularly when relative clauses (RCs) and prepositional phrases (PPs) admit multiple interpretations. While much research has examined native speakers or beginning L2 learners, little is known about how advanced learners apply formal syntactic knowledge to disambiguate such structures. This study addresses that gap by investigating how Indonesian EFL undergraduates resolve ambiguity using structural relation patterns—dominance, precedence, and c-command. A qualitative design was employed with 30 English Education majors who had completed a syntax course. Data were collected through tree-diagram tasks and a structured questionnaire, enabling structural and reflective insights. Findings revealed three main strategies: sorting by node, ignoring non-potential nodes, and using punctuation, with late closure as the most dominant approach. Structural analysis showed that while dominance and precedence guided parsing partially, c-command consistently supported accurate disambiguation when reinforced by semantic plausibility. Frequent reactivation also indicated that learners revised their interpretations when implausibility arose, demonstrating interactive rather than strictly structural parsing. The study contributes to syntactic theory by extending the role of c-command to advanced L2 contexts, parsing research by showing interactive strategy use, and pedagogy by advocating explicit instruction on structural relations combined with cognitive strategy training. These insights inform advanced grammar curricula and highlight the need for integrated approaches to ambiguity resolution in academic English.